Satellite Data Download Management with Uncertainty about the Generated Volumes - Pralet, Cédric; Verfaillie, Gérard; Maillard, Adrien; Hébrard, Emmanuel; Jozefowiez, Nicolas; Huguet, Marie-Jo; Desmousceaux, Thierry; Blanc-Paques, Pierre; Jaubert, Jean (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
Earth observation satellites are space sensors which acquire data, compress and record it on board, and then download it to the ground. Because of the use of more and more sophisticated compression algorithms, the amount of data resulting from an acquisition is more and more unpredictable. In such conditions, planning satellite data download activities offline on the ground is more and more problematic. In this paper, we report the results of a work aiming at evaluating the positive impact of planning downloads onboard when the amount of data produced by each acquisition is known. The data download problem to be solved on board is an assignment and scheduling problem with unsharable resources, precedence constraints, time-dependent minimum durations, and a complex optimization criterion. The generic InCELL library is used to model constraints and criterion, to check non temporal constraints, to propagate temporal constraints, and to evaluate the criterion. On top of this library, greedy and local search algorithms have been designed to produce download plans with limited time and computing resources available on board.